A centennial literature review (1919–2019) of research publications on land readjustment from a neo-institutional economic perspective. (September 2022) - LAI, Lawrence W.C.; DAVIES, Stephen N.G.; CHAU, K.W.; CHOY, Lennon H.T.; CHUA, Mark H.; LAM, Terry K.W.
Abstract: Informed by Coasian transaction cost reasoning from a neo-institutional economic perspective, this literature review identifies and examines 225 available research works involving 188 sets of author entries spanning from 1919 to 2019. All are on or connected with land readjustment, with a focus on lot boundaries as rigidly delineated. Over the years researchers and practitioners have considered and reconsidered land readjustment under various names in different forms (whether consensual or non-consensual among land owners affected) but almost invariably involving replotting of proprietary boundaries and reallocation of rights to realigned lots in a new layout as an alternative to state taking of land (eminent domain) or developer purchase of all properties. This literature review, connected with the adoption of a policy proposal, is unique in three ways as far as land readjustment is concerned. First, it has a time span of just over a century from 1919 to 2019 and traces works on Japan from the 1920s. Second, it cross-references the works reviewed. Third, it has a theoretical interest in property rights with a specific focus on boundaries as a dimension of those rights, and articulates land readjustment as a subset of the transfer of development rights. Fourth, it employs 'culturomics' (Michel et al. 2011, Roth 2014) in fathoming the context of the concept land readjustment and associated terms. Highlights: ● First systematic attempt to comprehensively review on land readjustment literature. ● Neo-institutional economics perspective in review. ● Textual reviews of 225 publications provided in supporting information.